PENGARUH UKURAN DEWAN KOMISARIS, KOMITE AUDIT, DAN KAP TERHADAP FEE AUDIT EKSTERNAL - Ayu, Putri Puspita; Septiani, Tika (Universitas Katolik Indonesia Atma Jaya, 2018)
This research aims to know the influence of the Board of Commissioners, the audit committee and the size of KAP partially towards the external audit fee. Data processing analysis is done by testing the effect of the independent variables on the dependent variable. Based on the results of the study, indicate that there is the influence of the size of the board of commissioners, the size of the audit committee and the size of KAP towards the external audit fee on financial sector service companies listed on the Indonesia stock exchange (BEI) in 2014-2016.